THE DYNAMICS OF THE GLOBAL PALM OIL AND SOYBEAN OIL ECONOMY IN MAJOR PRODUCING COUNTRIES - Nurachmat Herlambang; Zulkifli Alamsyah; Dompak Napitupulu; Adriani Adriani; Mirawati Yanita; Karina Rahmah (Fakultas Pertanian Universitas Mataram, 2026)
This study analyzes the economic dynamics of palm oil and soybean oil in major producing countries within the global vegetable oil market. The increasing global demand for vegetable oils has intensified production expansion, trade flows, and price fluctuations, particularly in countries that dominate world supply. This research aims to describe and examine trends in production, exports, and international prices of palm oil and soybean oil in the main producing countries over the period 1995–2024. The study employs a quantitative descriptive approach using time-series and comparative analysis based on secondary data from international statistical sources. The findings indicate that both commodities demonstrate strong long-term growth in production and export volumes, although characterized by significant price volatility driven by global demand shifts, trade policies, and external economic shocks. Palm oil production is highly concentrated in Southeast Asia, while soybean oil production is more geographically diversified. Despite fluctuations, both commodities remain strategic drivers of export revenue and agricultural sector growth in producing countries. The study concludes that the global vegetable oil market exhibits sustained expansion accompanied by structural vulnerabilities, requiring adaptive economic strategies to maintain stability and competitiveness.